Novel Role of Mitochondrial Matrix Metalloproteinase-2 in the Development of Diabetic Retinopathy - Mohammad, Ghulam (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. In the pathogenesis of diabetic retinopathy, retinal mitochondria become dysfunctional, their DNA is damaged, and capillary cells undergo accelerated apoptosis. Matrix metalloproteinase-2 (MMP2) becomes activated and proapoptotic, and the therapies that inhibit the development of diabetic retinopathy alleviate MMP2 activation. The authors sought to elucidate the possible mechanism by which activated MMP2 contributes to mitochondrial dysfunction. METHODS. The effect of the regulation of MMP2 on mitochondrial dysfunction and the subcellular localization of the molecular chaperone important for mitochondrial integrity (Hsp60) and gap junction protein connexin 43 were investigated in retinal endothelial cells. The results were confirmed in retinal mitochondria isolated from diabetic mouse overexpressing MnSOD and in the retinas of normal rats that received intravitreal administration of MMP2. RESULTS. High glucose increased MMP2 and decreased connexin 43 in the mitochondria of retinal endothelial cells. Although the Hsp60 gene transcript was increased, its abundance in the mitochondria was decreased, and its interaction with MMP2 was increased. In mice, the overexpression of MnSOD protected retinal mitochondria from diabetes-induced increases in MMP2 and decreases in Hsp60 and connexin 43. MMP2 administration in normal rats damaged the retinal mitochondria, decreased Hsp60 and connexin 43, and accelerated the apoptosis of retinal capillary cells. CONCLUSIONS. Elevated MMP2 in the mitochondria degrades its membranes by modulating Hsp60 and damaging connexin 43, and this activates the apoptotic machinery. Better understanding of MMP2-mediated mitochondrial damage could help identify new strategies for the treatment of this blinding disease.